2018
DOI: 10.1126/scisignal.aan3000
|View full text |Cite
|
Sign up to set email alerts
|

The transcription factor Lef1 switches partners from β-catenin to Smad3 during muscle stem cell quiescence

Abstract: Skeletal muscle stem cells (MuSCs), also known as satellite cells, persist in adult mammals by entering a state of quiescence (G) during the early postnatal period. Quiescence is reversed during damage-induced regeneration and re-established after regeneration. Entry of cultured myoblasts into G is associated with a specific, reversible induction of Wnt target genes, thus implicating members of the Tcf and Lef1 (Tcf/Lef) transcription factor family, which mediate transcriptional responses to Wnt signaling, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 93 publications
(130 reference statements)
0
30
1
Order By: Relevance
“…Earlier, we showed that quiescent myoblasts in culture display a distinct transcriptional profile, with altered signaling modules, in particular, enhanced Wnt-TCF signaling [12,23]. Interestingly, a number of ciliumassociated genes showed increased expression in G0.…”
Section: Primary Cilia Are Dynamically Regulated During the Cell Cyclmentioning
confidence: 84%
See 1 more Smart Citation
“…Earlier, we showed that quiescent myoblasts in culture display a distinct transcriptional profile, with altered signaling modules, in particular, enhanced Wnt-TCF signaling [12,23]. Interestingly, a number of ciliumassociated genes showed increased expression in G0.…”
Section: Primary Cilia Are Dynamically Regulated During the Cell Cyclmentioning
confidence: 84%
“…All assays were performed as described on stable clones expressing either the Super8X-TOP-flash (TCF site) construct, TFC-1, or the FOP-flash (mutated TCF site) construct [59], FFC-15. TFC-1 and FFC-15 clones were derived earlier [12,23].…”
Section: Luciferase Reporter Assays For Testing Wnt Pathway Activitymentioning
confidence: 99%
“…(Transforming growth factor beta-3) itself, TGF-beta receptor type-2 (TGFBR2) a receptor for the TGF-beta ligands TGFB1, TGFB2 & TGFB3 as well as; LEF1, that is associated with WNT-TCF/LEF and TGF-Beta-SMAD3 signalling in controlling muscle stem cell proliferation and self-renewal 64 . Finally, MECOM (alias EVI-1) has been demonstrated to play a role in growth regulation via TGF-beta/SMAD signalling 65 .…”
Section: Kegg Cancermentioning
confidence: 99%
“…TGFβ signaling has been shown, mainly in vitro , to negatively regulate myoblast differentiation through functional repression of the myogenic regulatory factors Myod1 21 and Myogenin 22 . However, TGFβ signaling has broader function in muscle cells, including quiescence 23 and activation 24 and the impact of TGFβ in syncytia formation has never been investigated. This lack in our knowledge mainly comes from the fact that the primary effects of TGFβ over-expression in skeletal muscles are development of endomysial fibrosis, due to its role as a potent growth factor for connective tissue cells 25,26 .…”
Section: Introductionmentioning
confidence: 99%